Penerapan Pembelajaran Blended Learning Pada Mata Pelajaran PPKn Kelas 12 Di SMA Tamansiswa Kota Mojokerto - Warsono Warsono; One Putra Firman Syah (Kajian Moral dan Kewarganegaraan, 2023)
In mid-2021, the COVID-19 pandemic outbreak experienced a decline which had an impact on the learning process at Tamansiswa High School, Mojokerto City. Therefore, an educational policy was established in the form of limited learning, namely the Blended Learning learning method at SMA Tamansiswa Mojokerto City. The purpose of this study is to describe the application of Blended Learning in the 12th grade Civics subject at SMA Tamansiswa Mojokerto City. The focus of the research is the application of Blended Learning in Civics subjects, the advantages and disadvantages of Blended Learning at SMA Tamansiswa Mojokerto City. This research uses qualitative research method with descriptive research type. There were four informants in this study who were selected using a purposive sampling technique with certain criteria. The data collection technique used was interviews and documentation which were carried out for one month. The data analysis technique uses interactive qualitative data analysis according to Miles and Huberman, namely data collection, data reduction and data presentation. The results of the study, namely the application of Blended Learning learning in Civics subjects were carried out through three stages, namely the planning stage with the preparation of Blended Learning RPP and socialization to educators and guardians of students, the implementation stage was carried out through distance learning and face-to-face learning in class and the evaluation stage in the form of assessment of student outcomes which includes assessment of attitudes, knowledge and skills. The advantage of Blended Learning is that it improves the quality of educators and students during the COVID-19 pandemic. The weakness in Blended Learning is the lack of attractiveness of students during distance learning. Keywords: Aplication, Blended Learning, Civics